Complex envelope crank-nicolson nearly PML algorithm for the left-handed material FDTD simulations - Ramadan, Omar (Springer/Plenum Publishers, 2007)
Unconditionally stable complex envelope (CE) absorbing boundary conditions (ABCs) are presented for truncating left handed material (LHM) domains. The proposed algorithm is based on incorporating the Crank Nicolson (CN) scheme into the CE finite difference time domain (FDTD) implementations of the nearly perfectly matched layer (NPML) formulations. The validity of the formulations is shown through numerical example carried out in one dimensional Lorentzian type LHM FDTD domain.
Keywords: complex envelope (CE); left handed material (LHM); Crank Nicolson (CN); finite difference time domain (FDTD); nearly perfectly matched layer (NPML)